Challenge in Biochemistry Courses: A Snapshot of Student Learning Difficulties - Ratulani Juwita; Asep Kadarohman; Norazilawati Abdullah; Heli Siti Halimatul Munawaroh (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2023)
Biochemistry with a broad and complex scope of material causes students to have difficulty in visualizing or understanding the concepts (metabolic pathways, molecular structures, and terms in biochemistry).This study aims to get an overview of students' learning difficulties in studying biochemistry. The study used a descriptive method. The research subjects were students of Biology Education at one of the universities in West Sumatra. The research instrument consists of a questionnaire of student opinions on learning difficulties and a test of mastery of concepts. It was found that 26.47% of students had difficulties in molecular structure material, 58.82% in metabolic pathway material, and 14.71% in term in biochemistry material. The students have difficulty in learning biochemistry concepts as shown by average lecture achievement score of 0.51 which is in a quite difficult range. The questionnaire results of student opinions on learning biochemistry show that 27% of students like learning using the practicum method.